Analisis Kinerja Pegawai Dalam Pelayanan Publik Pada Kantor Kelurahan Sawah Kecamatan Ciputat Kota Tangerang Selatan - Anggi Arinayanti; Rahmat Subur (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze employee performance in public services at Kelurahan Sawah, Ciputat District, South Tangerang City. Employee performance is considered important as it influences the quality of services in terms of speed, accuracy, and professionalism. The research adopts a descriptive qualitative approach using phenomenological methods focusing on actors (employees), social situations, and activities within the kelurahan environment. Data collection techniques included observation, interviews, documentation, Focus Group Discussion (FGD), and SWOT analysis. The findings indicate that employee performance has been relatively good, particularly in aspects of work quality, responsibility, and teamwork, which contribute to professional services and foster public trust. However, challenges remain in terms of work quantity, employee initiative, as well as limited physical facilities and empathy, which reduce service optimization. Overall, employee performance at Kelurahan Sawah plays a vital role in supporting effective public services, although continuous strategies are required to strengthen professionalism, improve service consistency, and develop a more adaptive work system aligned with community needs. Based on SWOT and FGD analysis, the most appropriate strategies to implement are Strength–Opportunities (S–O) and Weakness–Threats (W–T). The S–O strategy focuses on enhancing employee professionalism through the digitalization of public services, while the W–T strategy emphasizes strengthening work orientation and conducting regular briefings to maintain service consistency amid limited human resources and regulatory changes. The implementation of these strategies is expected to improve service quality, efficiency, and sustainability while simultaneously strengthening public trust in local government officials.